Compost-derived indole-3-acetic-acid-producing bacteria and their effects on enhancing the secondary fermentation of a swine manure-corn stalk composting. (March 2022) - Cai, Guanjing; Li, Junjie; Zhou, Mingdian; Zhu, Gefu; Li, Yanlin; Lv, Nan; Wang, Ruming; Li, Chunxing; Pan, Xiaofang
Abstract: Composting, as an effectively bio-oxidative process, has been widely used for converting organic waste to organic fertilizer. However, the low fertilizer efficiency of composting product limited its application in agriculture. To improve the growth-promoting effect of composting product, the present study investigated the bioaugmentation strategy of inoculating indole-3-acetic-acid (IAA)-producing bacteria. Firstly, two IAA-producing bacteria ( Bacillus safensis 33C and Rhodococcus rhodochrous YZ) were isolated from composting products with high IAA yields of 39.18 and 16.32 μg mL −1, respectively. Secondly, the microbial inoculants were prepared with 33C, YZ and a previously isolated IAA-producing strain Corynebacterium stationis 29B. To increase the accumulation of microbial secondary metabolites, microbial inoculants were amended at the secondary fermentation stage of composting. Physicochemical characterization showed that the maturity of composting product was significantly promoted by inoculating microbial inoculants prepared with 33C and 29B (single and combined inoculants). Finally, bioaugmentation with 33C and 29B increased the IAA contents of composting products by 2.9–5.2 times, which benefited the germination and early vegetative growth of plants. In summary, inoculating proper IAA-producing bacteria during secondary fermentation of composting could improve the quality of composting product and expand its application. Graphical abstract: Image 1 Highlights: Two IAA-producing bacteria were isolated from swine manure composts. IAA-producing bacteria were amended in the secondary fermentation of composting. Only proper IAA-producing bacteria would increase the compost quality significantly. IAA accumulated in the composts with the inoculation of IAA-producing bacteria. IAA accumulation benefited the germination and early vegetative growth of tomatoes.